Negotiation Communication for the Same-Clan Marriage in Batak Toba Tribe - Widya Septiana Simangunsong; Primada Qurrota Ayun, S.I.Kom, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
A same-clan marriage is basically prohibited in Batak Toba tribe but in some cases there are several couples did it. The different opinion of this issue triggers conflict for the couples and its surroundings. People nowadays consider that negotiation is the first step to set up a productive conflict where its conflict can be resolved by using the right communication. Couple who did same-clan marriage could negotiate the different point of view regarding this issue to form an agreement The writer used the interpretive paradigm and the data analysis technique as the phenomenology method of the study. The data of the study were three couples who did same-clan marriage. The theory used in this study was the Principled Negotiation from Fisher and the Win-win negotiation Strategies from Beebe et al. By using a qualitative approach, this study aims to determine several factors behind the occurrence of a same-clan marriage and the communication in negotiation of a same-clan marriage in Batak Toba tribe. The result of the study shows that there are 3 aspects of communication in negotiation of a same-clan marriage in Batak Toba tribe; language characteristics, the use of non-verbal communication, and the choice of communication line. When all the informant got involved in the negotiation process of a same-clan marriage, the study shows that mostly there is no decision for both sides. Through this study the writer concluded that the creation of an agreement when negotiating influenced by negotiations based on several principles; separating people from the problem, centered on interest not opinion, determination of choice for the mutual benefit and stands on an objective criteria which the negotiators negotiate through direct communication. The prepossessing result of the study shows that some clans in Batak Toba tribes no longer concern about the issue of a same-clan marriage.